Crisis Communication Strategies for Restoring Public Trust in Cash Waqf Management - Arif Heru Saputra; Nur'annafi Farni Syam Maella; Redi Panuju (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
The development of cash waqf in Indonesia demonstrates considerable potential as an Islamic social finance instrument; however, this potential has not been accompanied by optimal levels of public trust and participation. This condition presents challenges in cash waqf management, particularly regarding perceptions of transparency, accountability, and the effectiveness of institutional communication. These dynamics indicate a latent trust crisis evolving within the public communication sphere, especially across digital media platforms. This study aims to analyze crisis communication strategies implemented in the management of cash waqf at the Ministry of Religious Affairs and examine their role in restoring public trust. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, documentation, and observation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The analysis framework is grounded in crisis communication theory and the concept of public trust. The findings reveal that communication strategies remain largely reactive, focusing on issue clarification after crises emerge. Although efforts in transparency, digital communication, and positive narrative building are evident, they are not yet fully integrated. Public trust recovery depends on communication consistency, accountability, and accessible information delivery.